The development of an ancillary textile industry waste treatment process - Greenblau, Norman (Water Research Group, 2016)
The objective of this thesis is twofold - (1) to design the unit processes for treating the waste from a specific industrial plant using the best practicable technology, and (2) to critically examine the theory of these unit processes for utilization in design. The industrial waste was derived from a synthetic button and textile trimmings factory producing polyester and casein buttons. The effluent has a high pH and COD; contains metallic poisons; and is highly coloured. It exceeds the limitations for effluent quality promulgated by the Cape Town Municipality before discharge to the sewers. A certain measure of pretreatment before discharge to the sewers was therefore required. The treatment process eventually selected consists of neutralization; flocculation; sedimentation; sand filtration of the sludge; and atmospheric drying of the sludge.